The effects of different rates of nitrogen fertilizer and shade on physiological characteristics and yield of Basil (Ocimum tenuiflorum) - Niazi, Shahidullah; Sulaiman, Mohammad Firdaus; Sadat, Mohammad Ismail; Saleh, Ghizan; Nakasha, Jaafar Juju (Agri. Bio. Publishers, 2022)
The economic value of basil (Ocimum tenuiflorum) herb comes from its leaves; efforts to increase the number of leaves should be of high importance. This study was conducted to improve the growth and development of basil through investigation on the effects of applications of different rates of nitrogen (0, 100, 150 and 200 kg/ha) and percentage of shade (0, 50 and 70%). Results showed that the growth and development of basil responded to the different rates of nitrogen applications as well as the percentages of shade. Plants treated with 150 kg/ha N under 50% shade yielded the best results, reaching 48.8 cm in height, possessing the highest number of leaves (139 leaves/plant) and average leaf area (11.42 cm2/ leaf). It was also noticed that plants exposed to full sun light had the lowest plant height (34.55 cm), lowest number of leaves (120 leaves/plant) and lowest leaf area (5.40 cm2/leaf). The application of nitrogen at 150 kg/ha and 50% shade offered better development of leaves (number, leaf area and weight) with good development of root (weight, length and surface area). As the value of basil is on its leaves, therefore, the final recommendation is made based on the growth and development of its leaves.